Offloading Visual-Inertial Odometry for Low Power Extended Reality - Jiang, Qinjun; Huzaifa, Muhammad; Sentosa, William; Zhang, Jeffrey; Gao, Steven; Pang, Yihan; Godfrey, Brighten; Adve, Sarita (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Power consumption is a constraint in designing all-day wear extended reality (XR) devices. To reduce power consumption, we present a novel end-to-end XR system with visual-inertial odometry (VIO) offloaded to a remote server. Even with long network latency, the system produces an end-to-end XR experience comparable to a system without offloading while providing significant power savings. This latency and bandwidth-resilient nature of head tracking is a new and surprising result.